2020
DOI: 10.1364/prj.402555
|View full text |Cite
|
Sign up to set email alerts
|

Efficient emission of InGaN-based light-emitting diodes: toward orange and red

Abstract: Indium gallium nitride (InGaN)-based light-emitting diodes (LEDs) are considered a promising candidate for red-green-blue (RGB) micro displays. Currently, the blue and green LEDs are efficient, while the red ones are inefficient for such applications. This paper reports our work of creating efficient InGaN-based orange and red LEDs on silicon(111) substrates at low current density. Based on the structure of InGaN yellow LEDs, by simply reducing the growth temperature of all the yellow quantum wells (QWs), we o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
94
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 37 publications
4
94
2
Order By: Relevance
“…Because the QCSE and the band filling effect were respectively originated from the in-plane strain and In fluctuation in InGaN QWs, the strain relaxation and the improvement of the InGaN crystal quality were vital for suppressing this large blue-shift. The FWHM at the current density below 20 A/cm 2 remained 50-51 nm, which was comparable to the best values of other InGaN orange and red LEDs [15,27]. However, the FWHM increased to around 56 nm with a current density up to 100 A/cm 2 .…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Because the QCSE and the band filling effect were respectively originated from the in-plane strain and In fluctuation in InGaN QWs, the strain relaxation and the improvement of the InGaN crystal quality were vital for suppressing this large blue-shift. The FWHM at the current density below 20 A/cm 2 remained 50-51 nm, which was comparable to the best values of other InGaN orange and red LEDs [15,27]. However, the FWHM increased to around 56 nm with a current density up to 100 A/cm 2 .…”
Section: Resultssupporting
confidence: 81%
“…Recently, 6 × 6 µm 2 size 632-nm InGaN µLEDs on porous GaN were demonstrated to have an on-wafer EQE of 0.2%, which was the first reported value for red µLEDs with the dimension < 10 µm [14]. Besides, orange/red InGaN LEDs could realize high efficiency on silicon substrates [15] because the tensile strain of the GaN on silicon during growth was favorable for In incorporation [11]. Our group chose to adjust the thickness of the GaN on sapphire substrates to realize highly efficient InGaN red LEDs [16].…”
mentioning
confidence: 99%
“…By utilizing the benefits of V-pit to screen dislocations and enhance hole injection, Zhang and his co-works have created efficient InGaN-based LEDs with peak efficiency up to 24.0% at 0.8 A/cm 2 . However, the LED chips reported by Zhang et al is still limited to of tranditional size (1 mm × 1 mm), which is much larger than that of micro-LED [ 25 ]. Moreover, many works have reported that the internal quantum efficiency (IQE) and EQE of micro-LEDs decrease as the chip size is reduced [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this on-wafer EQE is the highest reported value for InGaN red µLEDs. Recently, a high wall-plug efficiency (WPE) of 16.8% at 621 nm was obtained at 0.8 A/cm 2 for 1×1 mm 2 InGaN-based LEDs [15]. This WPE value was the highest for standard InGaN red LEDs.…”
mentioning
confidence: 99%